Genome-Wide Estimates of Runs of Homozygosity, Heterozygosity, and Genetic Load in Two Chinese Indigenous Goat Breeds - Li, Guixin; Tang, Jianhong; Huang, Jinyan; Jiang, Yongchuang; Fan, Yin; Wang, Xiaopeng; Ren, Jun (Frontiers in Genetics, 2022)
Runs of homozygosity (ROH) and heterozygosity (ROHet) are windows into population demographic history and adaptative evolution. Numerous studies have shown that deleterious mutations are enriched in the ROH of humans, pigs, cattle and chickens. However, the relationship of deleterious variants to ROH and the pattern of ROHet in goats have been largely understudied. Here, 240 Guangfeng and Ganxi goats from Jiangxi Province, China, were genotyped using the Illumina GoatSNP50 BeadChip, and genome-wide ROH, ROHet and genetic load analyses were performed in the context of 32 global goat breeds. The classes with the highest percentage of ROH and ROHet were 0.5-2 Mb and 0.5-1 Mb, respectively. Results of inbreeding coefficients (based on SNP and ROH) and ROHet measurements showed that Guangfeng goats had higher genetic variability than most Chinese goats. While, Ganxi goats had a high degree of inbreeding, even exceeding that of commercial goat breeds. Next, the predicted damaging homozygotes were more enriched in long ROHs, especially in Guangfeng goats. Therefore, we suggest that information on damaging alleles should also be incorporated into the design of breeding and conservation programs. A list of genes related to fecundity, growth and environmental adaptation were identified in the ROH hotspots of two Jiangxi goats. A sense-related ROH hotspot (chromosome 12: 50.55-50.81 Mb) was shared across global goat breeds and may have undergone selection prior to goat domestication. Furthermore, an identical ROHet hotspot (chromosome 1: 132.21-132.54 Mb) containing two genes associated with embryonic development (STAG1 and PCCB) was detected in domestic goat breeds worldwide. Tajima’s D and BetaScan2 statistics indicated that this region may be caused by long-term balancing selection. These findings not only provide guidance for the design of conservation strategies for Jiangxi goat breeds, but also enrich our understanding of the adaptative evolution of goats.